Syringomatous Tumour Presenting as Inversion of a Supernumerary Nipple - Louise Öwall; Henrik Mygind; Åsa Rosenborg; Anne-Vibeke Lænkholm (Case Reports in Pathology)
Syringomatous tumour (SyT) is a rare type of benign locally infiltrative tumour with debated origin. Because of the growth pattern, SyT can be mistaken for a malignant tumour, and it is therefore important to keep this diagnosis in mind. This case presents a woman with two supernumerary nipples on each side of the abdomen. One of the nipples was inverted with a small palpable firm mass in close relation to the nipple, leading to referral to the breast surgery department. SyT occurring in a supernumerary nipple and presenting with the symptoms described in this case has to our knowledge never been described previously.